Effect of different isometric trunk extension intensities on the muscle stiffness of the lumbar and lower limbs - Zhang, Yuting; Chen, Mengtong; Liu, Hongxiu; He, Yanan; Li, Yuanchao; Shen, Peifeng; Chen, Yiming; Huang, Jiapeng; Liu, Chunlong (Frontiers in Physiology, 2024)
Purpose: To investigate the effect of isometric prone trunk extension (IPTE) contraction intensity on the stiffness of erector spinae (ES), semitendinosus (ST), biceps femoris (BF), and gastrocnemius muscles to understand the overall muscle mechanical behavior during IPTE and to explore the mechanisms of mechanical conduction in humans coordinated contraction of the body kinetic chain.Methods: Twenty healthy females were recruited, and participants underwent IPTE at three contraction intensities i.e. 0% maximum voluntary isometric contraction (MVIC), 30% MVIC, and 60% MVIC, and muscle stiffness was measured using MyotonPRO.Results: Muscle stiffness was moderately to strongly positively correlated with contraction intensity (r = 0.408-0.655, p < 0.001). The percentage increase in stiffness at low intensity was much greater in ES than in lower limb muscles and greater in ST and BF than in gastrocnemius, whereas at moderate intensity, the percentage increase in stiffness decreased in all muscles, and the percentage increase in stiffness in ES was lower than that in ST. There was a moderate to strong positive correlation between ES stiffness variation and ST (r = 0.758-0.902, p < 0.001), BF (r = 0.454-0.515, p < 0.05), MG (r = 0.643-0.652, p < 0.01), LG (r = 0.659-0.897, p < 0.01).Conclusions: IPTE significantly affected the stiffness of lumbar and lower limb muscles, and lowintensity IPTE activated the ES more efficiently. There was force transmission between ES, ST, andLG. There were significant coordinated muscle contractions between ES, ST, and LG. This provides preliminary evidence for exploring the overall modulation pattern of the lumbar and lower limb muscles' kinetic chains. In future studies, we will combine other stiffness assessment methods (such as Magnetic Resonance Elastography, Shear Wave Elastography, or electromyography) to corroborate our findings.